2020
DOI: 10.1177/0003489420950370
|View full text |Cite
|
Sign up to set email alerts
|

Recorded Flexible Nasolaryngoscopy for Neonatal Vocal Cord Assessment in a Prospective Cohort

Abstract: Objective: Assessing vocal cord mobility by flexible nasolaryngoscopy (FNL) can be difficult in neonates. To date, prospective studies evaluating the incidence and diagnostic accuracy of vocal cord paralysis (VCP) after surgical patent ductus arteriosus (PDA) ligation are limited. It is unknown whether video FNL improves diagnosis in this population. This study compared video recordings with bedside evaluation for diagnosis of VCP and determined inter-rater reliability of the diagnosis of VCP in preterm infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There was fair reliability between pediatric otolaryngologists viewing the videos (kappa = 0.75) with 91% agreement. 1 Liu et al evaluated 20 infants and assessed inter-rater reliability of video-recorded FFL and found substantial agreement on immobility versus normal mobility (kappa = 0.67), but only moderate reliability on the degree of immobility (kappa = 0.49). 2 Historically, US was considered limited by operatordependent image quality and interpretation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…There was fair reliability between pediatric otolaryngologists viewing the videos (kappa = 0.75) with 91% agreement. 1 Liu et al evaluated 20 infants and assessed inter-rater reliability of video-recorded FFL and found substantial agreement on immobility versus normal mobility (kappa = 0.67), but only moderate reliability on the degree of immobility (kappa = 0.49). 2 Historically, US was considered limited by operatordependent image quality and interpretation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Initial FFL identified six patients with VFI and an additional three patients were found to have immobility on review of the video (initially thought to have normal mobility). There was fair reliability between pediatric otolaryngologists viewing the videos (kappa = 0.75) with 91% agreement 1 . Liu et al evaluated 20 infants and assessed inter‐rater reliability of video‐recorded FFL and found substantial agreement on immobility versus normal mobility (kappa = 0.67), but only moderate reliability on the degree of immobility (kappa = 0.49) 2 …”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In small children, while the interobserver agreement between normal versus abnormal vocal cord movement on flexible nasopharyngolaryngoscopy is substantial, the agreement between the degree of movement of the vocal cord (paralysis vs. paresis) is only moderate [30]. A recent publication suggested that video recording flexible nasopharyngolaryngoscopy exams improves diagnostic accuracy of vocal cord paralysis in neonates [31].…”
Section: Endoscopic Evaluation Of Vocal Cord Paralysismentioning
confidence: 99%